Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) \(60\%x+\frac{2}{3}x=\frac{1}{3}.6\frac{1}{3}\)
=> \(\frac{3}{5}x+\frac{2}{3}x=\frac{19}{9}\)
=> \(\frac{19}{15}x=\frac{19}{9}\)
=> \(x=\frac{19}{9}:\frac{19}{15}\)
=> \(x=\frac{5}{3}\)
b) (-0,6x - 1/3) . 3/5 - (-1) = 1/3
=> (-3/5x - 1/3) .3/5 = 1/3 - 1
=> (-3/5x - 1/3).3/5 = -2/3
=> -3/5x - 1/3 = -2/3 : 3/5
=> -3/5x - 1/3 = -10/9
=> -3/5x = -10/9 + 1/3
=> -3/5x = -7/9
=> x = -7/9 : (-3/5)
=> x = 35/27
a,60%x+2/3x=1/3.6 1/3
x(60%+2/3)=19/6
x.19/15=19/6
x=19/6 : 19/15
x=5/2
b,[-0,6x-1/2].3/4-(-1)=1/3
(-3/5x-1/2).3/4=1/3-1
(-3/5x-1/2).3/4=-2/3
-0,6x-0,5=-2/3:3/4
................................
c,2[1/2x-1/3]-3/2=1/4
....................................... (tương tự...)
d,Số đó là:720% : 2/3=10,8
Ta có : 7(x - 1) + 2x(x - 1) = 0
<=> (2x + 7)(x - 1) = 0
\(\Leftrightarrow\orbr{\begin{cases}2x+7=0\\x-1=0\end{cases}}\)
\(\Leftrightarrow\orbr{\begin{cases}2x=-7\\x=1\end{cases}}\)
\(\Leftrightarrow\orbr{\begin{cases}x=-\frac{7}{2}\\x=1\end{cases}}\)
6x . 6 = 2016
6x = 2016 : 6
6x = 336
=> x \(\in\varnothing\)
42x+3 : 4 = 256
42x+3 = 256 x 4
42x+3 = 1024
42x+3 = 45
2x + 3 = 5
2x = 5 - 3
2x = 2
x = 2 : 2
x = 1
[ x - 2 ]2 = 16
[ x - 2 ]2 = 42
x - 2 = 4
x = 4 + 2
x = 6
[ 2x - 1 ]3 = 27
[ 2x - 1 ]3 = 33
2x - 1 = 3
2x = 3 + 1
2x = 4
x = 4 : 2
x = 2
[ 2x - 1 ]100 = [ 2x - 1 ]100
=> x \(\in N\)
a,\(\left(x-1\right)^2=4=2^2=\left(-2\right)^2\)
\(\Rightarrow\orbr{\begin{cases}x-1=2\\x-1=-2\end{cases}\Rightarrow\orbr{\begin{cases}x=3\\x=-1\end{cases}}}\)
b,\(\left(2x+1\right)^3=27=3^3\)
\(\Rightarrow2x+1=3\Rightarrow x=1\)
c,\(\left(2x-1\right)^5=x^5\Rightarrow2x-1=x\Rightarrow x=1\)
\(a,\left(x-1\right)^2=4\)
\(\Rightarrow x-1=2\)
\(\Rightarrow x=3\)
\(b,\left(2x+1\right)^3=27\)
\(\Rightarrow2x+1=3\)
\(\Rightarrow x=1\)
\(c,\left(2x-1\right)^5=x^5\)
\(\Rightarrow2x-1=x\)
\(\Rightarrow2x-x-1=0\)
\(\Rightarrow x=1\)
Học tốt!
ai trả lời trức thì tick cho một sao
\(\left(2x-1\right)^4=3.6^2-27\)
\(\Leftrightarrow\left(2x-1\right)^4=81\)
\(\Leftrightarrow\left(2x-1\right)^2=9\)
\(\Leftrightarrow\left[{}\begin{matrix}2x-1=3\\2x-1=-3\end{matrix}\right.\)
\(\Leftrightarrow\left[{}\begin{matrix}x=2\\x=-1\end{matrix}\right.\)